The Concept of Sustainable Development: the Basis for the Emergence of Integrated Reporting of the Enterprise - Bezverkhiy, K. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The sustainable development of societies, countries, economic sectors or business enterprises is based on the assumption that economic growth, production and consumption has the limitations imposed by the possibility for rehabilitating ecological systems. Issues of the rational use of resources form the conceptual framework for the sustainable development. But the emergence of information support in form of integrated reporting of the enterprise causes much debate in the theoretical and practical field. The purpose of the study is to analyze the evolution of the provisions of the sustainable development concept and identify the preconditions for the emergence of integrated reporting of the enterprise. The components of the sustainable development and its purpose are highlighted; the sustainable development goals of UN and their respective indictors are illustrated. The relation of the categories of capital (financial, industrial, intellectual, human, social and nature capital), reflected in the integrated reporting of the enterprise, with the sustainable development goals is substantiated. The analysis shows that the top category of capital contributing in all the sustainable development goals (the total of 17) is social capital; financial capital (contributing in 14 goals) ranks second, human capital (12 goals) ranks third, production capital (10 goals) comes fourth, intellectual capital (9 goals) is the fifth, and nature capital (8 goals) ranks sixth. These results are indicative of high relevance of integrated reporting of the enterprise to the sustainable development goals.